NGHIÊN CỨU CHẾ TẠO XỐP PU/GRAPHITE HẤP THỤ NHIỆT - Lê, Chí Thành; Mai, Đức Huynh; Trần, Hữu Trung; Lê, Trọng Lư; Phan, Ngọc Hồng; Bùi, Duy Ngọc; Nguyễn, Vũ Giang (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
STUDY ON EFFECT OF COMPONENTS RATIO ON THE PROPERTIES OF POLYURETHANE/GRAPHITE COMPOSITE APPLLIED AS SOLAR ENERGY ADSORPTION MATERIAL This paper presents the effect of MDI/PPG ratio, polydimethylsilosane surfactant content and graphite content on the mechanical properties of the PU/graphite composites in order to finding the most suitable content of components to prepare the PU/graphite composite having good properties. The obtained results showed that the tensile strength and compressive strength of the PU/graphite composite reached the highest value at the MDI/PPG ratio of 1.15/1 and polydimethylsilosane content of 0.8%. The high graphite weight can cause the decrease in compressive strength and tensile properties of the PU/graphite composites. However, the increase in graphite content in the composites can lead to improve in the solar energy adsorption ability of the composites significantly. This confirmed that the potential using of graphite as filler for PU to prepare the porous materials having good solar energy adsorption ability.